Avaliação da gentamicina aplicada em ovos de aves reprodutoras pesadas e seu efeito residual nos tecidos - Magenis, Giovana Bongiolo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The concern of the poultry industry to maintain high levels of productivity and food security has spurred preventive actions in order to prevent the introduction of pathogens in the poultry system. The use of gentamicin associated with in ovo vaccination has been widely used for this purpose. In particular, there is little information available in the literature about the clinical and food safety of gentamicin when applied in ovo. Given this, two experiments were conducted to evaluate the effect of the administration of gentamicin in eggs of breeders in physical, hematological and biochemical parameters, as well as the permanence of this antimicrobial in broiler tissues. In the first study, 200 eggs of Cobb arrays were used and, in the 18th day of incubation, 100 eggs received only vaccination against Marek's disease (CG) and the other 100 received the vaccine with 0.22mg/egg of gentamicin sulfate (GT). After the birth (D0), physical examinations were performed at times D+3, D+6, D+10, D+14 and D+21 (3, 6, 10, 14 and 21 days after birth, respectively), as well as additional tests on D+6, D+10, D+14 to D+21. The physical parameters covered weighing, evaluation of body condition, behavior, posture/gait, breathing, appetite, feces, feathers and skin, as well as signs of intoxication. As for the laboratory parameters, the complete blood count and serum biochemical tests [urea, uric acid, aspartate aminotransferase, alanine aminotransferase (ALT), gamma glutamyl transferase (GGT), creatine kinase, albumin and total plasma proteins] were determined. The results were statistically analyzed using the General Linear Models Procedure (GLM) of SAS with Tukey's test, with a significance level of 5%. In both groups, all birds showed healthy throughout the study and the average body weight was not significantly different between GC and GT. In the complete blood count, despite variations within the same treatment, no significant differences between ...

A preocupação da indústria avícola em manter altos índices de produtividade e de segurança dos alimentos fez com que surgissem ações preventivas a fim de evitar a introdução de patógenos no sistema avícola. O uso de gentamicina associada à vacinação in ovo tem sido amplamente utilizada com essa finalidade. Neste particular, são escassas as informações disponíveis na literatura acerca da segurança clínica e alimentar da gentamicina quando aplicada in ovo. Diante disto, dois experimentos foram conduzidos para avaliar o efeito da administração da gentamicina em ovos de reprodutoras pesadas nos parâmetros físicos, hematológicos e bioquímicos, e também a permanência desse antimicrobiano nos tecidos de frangos de corte. No primeiro estudo, foram utilizados 200 ovos de matrizes da linhagem Cobb e, aos 18 dias de incubação, 100 ovos receberam apenas a vacina contra a doença de Marek (GC) e os outros 100 receberam a vacina juntamente com 0,22mg/ovo de sulfato de gentamicina (GT). Após o nascimento (D0), foram realizados exames físicos nos momentos D+3, D+6, D+10, D+14 e D+21 (3, 6, 10, 14 e 21 dias após o nascimento, respectivamente), assim como exames complementares em D+6, D+10, D+14 e D+21. Os parâmetros físicos compreenderam pesagem, avaliação da condição corpórea, comportamento, postura/marcha, respiração, apetite, excretas, penas e pele, bem como sinais de intoxicação. Quanto aos parâmetros laboratoriais, foram determinados o hemograma completo e as provas bioquímicas séricas [ureia, ácido úrico, aspartato aminotransferase, alanina aminotransferase (ALT), gama glutamiltransferase (GGT), creatina quinase, albumina e proteínas plasmáticas totais]. Os resultados foram submetidos à análise estatística por meio do procedimento general Linear Models (GLM) do SAS com pós-teste de Tukey, considerando o nível de significância de 5%. Em ambos os grupos, todas as aves se apresentaram saudáveis...
Keywords: Frango de corte; Ovos; Gentamicina; Tecidos (Anatomia e fisiologia) - Analise; Vacinação; Vacinas; Gentamicin